Biopebble Containers: DNA‐Directed Surface Assembly of Mesoporous Silica Nanoparticles for Cell Studies. Issue 20 (15th April 2019) - Sun, Pengchao; Leidner, Arnold; Weigel, Simone; Weidler, Peter G.; Heissler, Stefan; Scharnweber, Tim; Niemeyer, Christof M.
Abstract: The development of methods for colloidal self‐assembly on solid surfaces is important for many applications in biomedical sciences. Toward this goal, described is a versatile class of mesoporous silica nanoparticles (MSN) that contain on their surface various types of DNA molecules to enable their self‐assembly into micropatterned surface architectures useful for cell studies. Monodisperse dye‐doped MSN are synthesized by biphase stratification and functionalized with an aptamer oligonucleotide that serves as gatekeeper for the triggered release of encapsulated molecular cargo, such as fluorescent dye rhodamine B or the anticancer drug doxorubicin. One or two additional types of oligonucleotides are installed on the MSN surface to enable DNA‐directed immobilization on solid substrates bearing patterns of complementary capture oligonucleotides. It is demonstrated that this strategy can be used for efficient self‐assembly of microstructured surface architectures, which not only promote the adhesion and guidance of cells but also are capable of affecting the fate of adhered cells through triggered release of their cargo. It is believed that this approach is useful for diverse applications in tissue engineering and nanobio sciences. Abstract : DNA‐directed self‐assembly of mesoporous silica nanoparticles (MSN) on patterned surfaces can be used for efficient self‐assembly of microstructured surface architectures. The patterns promote the adhesion and guidance of cells and they are capable of affecting the fate of adhered cells through triggered release of MSN cargo.